Corrosion Assessment of Zn-Rich Epoxy Primers With Carbon Nanotube Additions in an Electrolyte With a Bacteria Consortium - Castaneda, Homero; Galicia, Monica (Frontiers in Materials, 2019)
Multifunctional coatings for corrosive environments have been developed to include two basic principle protection mechanisms: a barrier mechanism acting as a mass transfer process blocker, and cathodic protection mechanism acting as a charge transfer process promoter. Both mechanisms were assessed for Zinc-Rich Epoxy (ZRE) coatings in the presence of Carbon Nanotubes (CNTs) and exposure to a bioelectrolyte in order to study the evolution process during microbial corrosion conditions. The purpose of this study is to characterize in a comprehensive experimental platform the electrochemical response of a dual-protection zinc epoxy coating with different ratios of additive carbon nanotubes to active zinc particles upon exposure to a sulfate reducing consortium. Carbon nanotubes addition was found to affect both the prevailing mechanism at the coating interfaces and the formation of a biofilm at the coating surface that influenced the relatively dominance of the barrier protection mechanism. These multifunctional coatings with active particles could help to balance the charge transfer efficiency in terms of the sacrificial of zinc and barrier mechanisms, which influence biofilm formation and have potential consequences for biocorrosion on carbon steel.